ANALISIS YURIDIS TERHADAP PUTUSAN MK NOMOR 46/PUU-VIII/2010 TENTANG PENGAKUAN STATUS ANAK LUAR KAWIN DALAM PERSPEKTIF HUKUM ISLAM - AHMAD MAULANA (PREMISE LAW JURNAL, 2016)
A child is a trust given by God, therefore, he should have full attention and good care. But the birth of a baby in a family doesn’t always bring happiness, an illegitimate child will be a complex problem and cause alarm for the woman who delivers him, his biological father, and the community who live in the vicinity of the house. The rulling of the constitutional court of the Republic of Indonesia no. 46/PUU_VII/2010 has caused the problem for an illegitimated child to become apparent by the acceptance of the request for judicial review of the provision in article 43 pragraph 1 of law on marriage, related to the recognition of the illegitimate child. The consideration of the Constitutional Court in enacting the rulling is merely for the sake of the righteousness for the rights of an illegitimate child to be treated humanly and to guarantee his equal rights to the other children. Keywords : UUP No 1/1974, MK’s Ruliing No. 46/PUU-VIII/2010, Illegitimate Child, Islamic Marriage Law.